THE ROLE OF CATECHOLAMINES IN THE DEVELOPMENT OF IMMUNOSUPPRESSION IN SEVERE TRAUMATIC BRAIN INJURY - Тамара Ивановна Борщикова; Наталья Николаевна Епифанцева; Сергей Людовикович Кан; Сергей Николаевич Филимонов (Медицина в Кузбассе)
Objective. In the study included 45 patients with isolated severe traumatic brain injury in the acute period of this disease. Two groups were identified: the first group – 20 surviving patients, the second group – 25 deceased patients. The study to shown the role of catecholamines in the development of immunosuppression in the acute period of the severe traumatic brain injury.